The Tradition of Leumang Padé in Nagan Raya, Aceh (A Case Study in Gampong Cot Peuradi, Suka Makmue District) - Manan, Abdul; Ibrahim, Arfah; Alvinda, Salsa Billa (Prodi Sosiologi FISIP Universitas Teuku Umar, 2025)
The leumang padé tradition is one of the traditions carried out by the people of Gampong Cot Peuradi, Suka Makmue District, Nagan Raya regency which can be seen during the rice growing season. This is a form of expression of gratitude and hope to Allah SWT so that rice plants will be protected from pest attacks. The study aims at understanding the process of the leumang padé tradition, analyze its meaning, and understand its position in the contemporary context. The research approach used is descriptive qualitative research. Data was collected through observation, interviews, and documentation. Data obtained in the field was analyzed by reducing the data, presenting the data, and drawing conclusions. The results show that the leumang padé tradition is carried out twice a year when the rice begins to fill. This tradition is carried out by farmers cultivating the rice fields and the surrounding community to prevent disease and pests in the rice fields. The leumang padé tradition has its meaning, namely the meaning of gratitude, the meaning of social interaction, and the meaning of the ceremony. Its position is very important in the community's view because this tradition is their way of expressing gratitude to Allah SWT for the blessings given to them. Therefore, this tradition is still maintained and preserved to this day.